An Overview of Small-Scale Farmers in Vegetable Production in Three Districts in Suriname - Wasudha, M. S.; Ori, L.; Vanwing, T. (International Journal of Agricultural Technology, 2018)
Caribbean states dependent on agricultural imports to secure the food and nutrition is needed by their population. Although Suriname, a former Dutch colony, covers 80% of tropical forest, suitable land areas for agriculture are not optimally used to produce the needed vegetables. The purpose of the study was to provide an overview of the vegetable production and to get a better understanding of the status and problems of the small-scale vegetable farmer in Suriname. To collect the data, a descriptive study was conducted to generate information about the current status of small-scale farmers in Suriname over the period 2012-2015. Results revealed that the agricultural production is low, the information flow from agricultural institutions to the farmer is minimal and that vegetable farmers are facing many challenges when producing food for local and international markets.